Technology innovation in photo surveying for the knowledge, the documentation and the valorization of cultural heritage - Cardaci, Alessio; Versaci, Antonella (DISEGNARECON, 2013)
Since the early days of its invention, photography has played an essential role in the representation of architecture. Characteristic of our time, it has allowed a new view on the world and the establishment of a new language that has fully invested even the cultural heritage sector, proving to be an invaluable means for their knowledge, conservation and documentation. As a useful tool for the metric survey, the role of photography has gradually evolved as a function of objectives increasingly attentive not only to the architectural objects in themselves, but also to their relationships with space. The focus, therefore, is also gradually moved on before neglected aspects and photography has adapted, even technologically, to new purposes. This work aims to investigate these aspects, highlighting the peculiarities.